Chinua Achebe and Postcolonial Ambivalence: Gratitude and Revenge in Things Fall Apart, No Longer at Ease, and Arrow of God - Abussamen, Amneh K.; Neimneh, Shadi S. (American Journal of Creative Education, 2017)
This article aims at showing postcolonial ambivalence in Chinua Achebe’s first three novels: Achebe (1958); Achebe (1960) and Achebe (1964). Postcolonial ambivalence appears in the wavering position the texts exhibit between taking revenge on missionaries and natives and gratitude for them, which is revealed in the way the novels treat the themes of language, tolerance, religion and cultural violence. Gratitude for the missionaries and the natives appears in praising their languages, tolerance, religions, and justifying their violence. By contrast, the novels depict the revenge position on both missionaries and natives by criticizing English language and excluding Igbo language, criticizing the mutual intolerance of natives and missionaries, criticizing Christianity and Igbo religion, and portraying the unjustified cultural violence natives and missionaries practice. The pattern is traced to illustrate different levels of ambivalence in Achebe’s novels. Moreover, theories of ambivalence in postcolonial discourse and partial representation are relevant. The conclusion suggests reasons for postcolonial ambivalence in Achebe’s novels, revealing an ironic twist in his fictions and exposing the writer's cynical attitude toward the difficult position of the native intellectual trapped between two cultures. Our approach is applicable to a range of recent postcolonial literary works with ambivalent attitudes, and to the works of writers living in hybrid cultures. This article also connects postcolonial, postmodern, and post-structuralist theories on the basis of their common notions of ambivalence/indeterminacy.